Hypercentral groups of finite subnormal rank - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We introduce the notion of subnormal rank of a group and study hypercentral groups of finite subnormal rank. We construct an example of a hypercentral group that has a finite subnormal rank and infinite (special) rank.